What predicts health students’ self-reported preparedness to work in Indigenous health settings? - Bullen, Jonathan; Roberts, Lynne; Hoffman, Julie (Springer, Netherlands, 2017)
Australian undergraduate programs are implementing curriculum aimed at better preparing graduates to work in culturally diverse settings, but there remains uncertainty over the role of extant student attitudes towards Indigenous Australians. To begin to address this, we obtained baseline data on student attitudes upon entry to tertiary education. 1175 health science first-year students (275 males, 897 females) completed an anonymous in-class paper questionnaire. On average, students reported positive attitudes towards Indigenous Australians, with female students reporting more positive attitudes than male and domestic students more positive than international. Hierarchical multiple regression analyses indicated that after controlling for demographic variables, interactional diversity experiences and attitudes accounted for significant variance in a range of measures of preparedness to work in Indigenous health contexts. The knowledge gained will inform the development of, and alignment between, curriculum and pedagogical approaches, leading to an improved facilitation model for educators in the Indigenous Studies context.